Extracellular Vesicles as a New Promising Therapy in HIV Infection - Navarrete-Muñoz, Maria A.; Llorens, Carlos; Benito, José M.; Rallón, Norma (Frontiers in Immunology, 2022)
Combination antiretroviral therapy (cART) effectively blocks HIV replication but cannot completely eliminate HIV from the body mainly due to establishment of a viral reservoir. To date, clinical strategies designed to replace cART for life and alternatively to eliminate the HIV reservoir have failed. The reduced expression of viral antigens in the latently infected cells is one of the main reasons behind the failure of the strategies to purge the HIV reservoir. This situation has forced the scientific community to search alternative therapeutic strategies to control HIV infection. In this regard, recent findings have pointed out extracellular vesicles as therapeutic agents with enormous potential to control HIV infection. This review focuses on their role as pro-viral and anti-viral factors, as well as their potential therapeutic applications.